Difference and Discipline: The Cage/Cunningham Aesthetic Revisited. - Perloff, Marjorie (Contemporary Music Review, 2012)
Indeterminacy, fluidity, anarchy, the non-hierarchical, the multiplex: these have usually been understood as the attributes of John Cage's and Merce Cunningham's musical and dance pieces, so many of which were made in collaboration. But to study the works themselves rather than the artist's statements of intention is to understand that theirs is in fact a simulated or regulated anarchy, a ‘natural’ form that turns out to be highly controlled and designed by the two artists. What Cage called ‘purposeless play’—‘a way of waking up to the very life we're living’—is planned down to the last detail as is Cunningham's choreography of decenteredness and “natural” movement. What is presented as open form turns out to be a rule-based practice. Indeed, it is the very combination of authorial control and simulated anarchy that makes such works as Roaratorio (Cage) and Walkaround Time (Cunningham) genuinely new, subversive, and radical vis-à-vis earlier music and dance. These works, with their renewal of what Marcel Duchamp called the infrathin, thus provide paradigms for avant-garde practice in the late twentieth century.